Prediction of cardiovascular disease for the elderly - Ho, Bryan En Hao (Nanyang Technological University, 2022)
Cardiovascular disease is the number one cause of death across the globe. With over 17 million people's deaths caused by cardiovascular diseases in 2019 alone. This represents about 32% of all global deaths [1]. Coupled with the increasing cost of health care services, the need for costly yearly health checks is not always accessible to everyone. Hence, the lack of less invasive and cost-effective health monitoring measures is a call for concern. This report is the report for the Final Year Project, “Prediction of Cardiovascular Disease for the Elderly”. The purpose of this report is to document the project progression, achievements and problems faced up to date and possible future studies. This report is 40 pages, excluding cover pages, abstract, and references. This project aims to create a means of cost-effective health monitoring for the elderly’s cardiovascular health and utilize neural network algorithms to predict their chance of cardiovascular disease.